Credit score doctors - Luojia Hu; Xing Huang; Andrei Simonov (Federal Reserve Bank of Chicago, 2020)
We study how the existence of cutoffs in credit scores affects the behavior of homebuyers. Borrowers are more likely to purchase houses after their credit scores cross over a cutoff to qualify them for a higher credit score bin. However, the credit accounts of these individuals (crossover group) are more likely to become delinquent within four years following home purchases than the accounts of those who had stayed in the same bin (non-crossover group). The effect is not only concentrated in subprime bins, but in other bins as well. It is neither limited to pre-crisis period nor curtailed by post-bust reforms. Using recent house price growth to proxy for the incentives for home purchases, we find that the gap in the delinquency rates between crossover and non-crossover groups is larger for areas with higher recent house price growth. Overall, our results indicate that the credit score at the time of home purchase may not be sufficiently informative because of individuals' strategic behavior, and suggest the importance of using the longer history of credit scores rather than just the latest draw in making lending decisions.
Keywords: 330